PENGARUH INDENPENDENSI DAN PROFESIONALISME AUDITOR TERHADAP KINERJA AUDITOR GUNA MEMPERTAHANKAN KUALITAS AUDIT - Ahmad Mukoffi; Yosepha Cristina Perawati; Sukarno Himawan Wibisono (Unitri Press, 2021)
This study aims to determine how the influence of independent variables and auditor professionalism on auditor performance. The type of data that has been used in this study was quantitative data with 60 samples of public accounting firms in East Java. The population in this study were 150 auditors using the purposive random sampling method obtained using a good questionnaire to be analyzed using SPSS version 26. The results of this study indicate that the independent variable and professionalism The independent variable shows a t-count value of 6.459 with a significance of 0.025 0.05, and the professionalism variable has a value of 3,460 with a significance of 0.000 which shows the effect on auditor performance. The auditor has a significant positive effect on the auditor's performance which shows that the independent and professional attitude of the auditor is an attitude that must be possessed by an auditor in carrying out an audit.